The Influence of Online Visual Merchandising and Customized Cross-Selling on Traveloka Mobile Apps Intention to Reuse: With Mediation of Visual Cues and Dynamic Personalization - Ariawan, Nathania Putri; Ariadi, Gede (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2025)
This study examined the impact of Online Visual Merchandising (OVM) and Customized Cross Selling (CCS) on the Intention to Reuse (ItR) Traveloka’s mobile app, mediated by Visual Cues (VC) and Dynamic Personalization (DP). With the increasing competition in the online travel industry and the need for platforms to retain users, understanding the factors that drive repurchase intentions is crucial. A survey of 135 app users aged 25-40 was conducted, and data were analyzed using PLS-SEM. Results indicate that while OVM alone did not significantly affect ItR, CCS had a positive impact. VC and DP significantly mediated the relationships between OVM, CCS, and ItR. The findings suggest that aesthetic elements alone are insufficient for driving repetitive behavior; instead, a strategic integration of visual, personalized, and cross selling strategies is crucial. The study supports nudge theory and offers practical insights for optimizing digital commerce applications to enhance repurchase intentions.